ISSLS Prize winner: The anatomy of failure in lumbar disc herniation: an in vivo, multimodal, prospective study of 181 subjects - Rajasekaran, S; Bajaj, Nipun; Tubaki, Vijay; Kanna, Rishi M; Shetty, Ajoy Prasad (Spine (Philadelphia, Pa. 1976), 2013)
A prospective multimodal study including clinical, radiological, serial postcontrast magnetic resonance imaging, intraoperative findings, and histopathological study. To document in vivo, the site of anatomical failure in lumbar disc herniation (LDH). Although in vitro mechanical disruption studies have implicated both the endplate junction (EPJ) and the annulus fibrosus (AF) as the site of failure in LDH, there are no in vivo human studies to document the exact anatomy of failure. One hundred eighty-one consecutive patients requiring microdiscectomy at a single level formed the study group. The status of the endplate and AF in the operated level (study discs) and the other discs (control) were evaluated by plain radiograph, thin slice computed tomographic scan, plain and contrast magnetic resonance imaging, intraoperative examination, and histopathological analysis. LDH due to EPJ failure (EPJF- type I herniation) was more common (117; 65%) than annulus fibrosis rupture. Herniated discs had a significantly higher incidence of EPJF than control discs (P < 0.0001). The EPJF was evident radiologically as vertebral corner defect in 30 patients, rim avulsion in 46, frank bony avulsions in 24, and avulsion at both upper and lower EP in 4. Thirteen discs with normal EP radiologically had cartilage or bone avulsion intraoperatively. Sixty-four discs (35%) had intact EP of which annular high intensity zone was found in 21 (11%), suggesting a disruption of AF (type II herniation). Postcontrast magnetic resonance image of 20 patients showed dye leak at the EPJ proving EPJF as main cause of LDH. Our study provides the first in vivo evidence that LDH in humans is more commonly the result of EPJF than AF rupture and offers clinical validation of previous in vitro mechanical disruption studies. Future research must focus on the EPJ as a primary area of interest in LDH. N/A.